Knowledge and Its Legitimacy, an Exploratory (Meta)Ethical Framework-Based Analysis of Narratives on Coastal Flooding Risks in a Changing Climate - Vanderlinden, Jean-Paul; Rouhaud, Estelle; Touili, Nabil (Frontiers in Climate, 2022)
Knowledge quality assessment has been developed in order to analyze knowledge in situations of high stakes and urgency when characterized by deep uncertainty and ignorance. Governing coastal flood risk in the face of climate change is typical of such situations. These are situations which limit the ability to establish objective, reliable, and valid facts. This paper identify the ethical frameworks that stakeholders use to judge flood risk situations under climate change, and infer from these knowledge legitimacy criteria. Knowledge legitimacy, defined as being respectful of stakeholders’ divergent values and beliefs, is one of the three broad quality criteria that have been proposed in order to assess knowledge quality in such situations; credibility (as scientific adequacy) and salience (relevance to the needs of decision makers) being the two others. Knowledge legitimacy is essentially the subject of a literature analyzing, ex-post (once knowledge has been deployed), how stakeholders’ participation contributes to knowledge legitimacy. Very little is known about characteristics that could be observed before knowledge is deployed. In this paper we posit that this blind spot may be addressed. In order to achieve this we first identify the ethical frameworks that stakeholders use to judge a situation of risk under rapidly changing conditions. We then associate these ethical frameworks to characteristics of knowledge. We tested this conceptualization through a case study approach centered on flood risk on the French Atlantic coast. We analyzed two diachronic corpora consisting of interviews conducted in 2010-12 (33 interviews) and 2020 (15 interviews). These were approached as narratives of a risk situation. We coded these along themes, predefined (deontology, consequentialism, virtue ethics) and emerging (discourse ethics, connection ethics, and a naturalistic ethic). When faced with flood risks, stakeholders mobilizes several metaethical frameworks as procedural and substantive guiding principles. In order to respect what we interpret as manifestations of the moral stances of stakeholders, our results indicate that knowledge legitimacy may be assessed against lability, debatability and adaptability; degree of co-production; place-baseness; attention to nature. The operationalization of these criteria as the knowledge that is used for decision making is increasingly contested on the ground of its legitimacy.